Some Initial Observations Concerning the African Wild BananaEnsete ventricosumasa Resource for Vertebrates - Ssali, Fredrick; Sheil, Douglas (Institute of Tropical Forest Conservation, 2019)
The ecological role and significance of “African wild bananas”Ensete ventricosum (Welw.) Cheesman (Musaceae) are unknown.We considered if E. ventricosum, with its sustained flowering and fruiting, might act in some ways like a keystone species by supporting animal populations during periods of resource scarcity. We deployed camera traps facing flowers or fruits of E. ventricosumfor a total of 40 camera months in the Bwindi Impenetrable National Park, Uganda. We recorded 1,691 visitor events by 11 vertebrate species to flowers and fruits (1,129 events by five species to flowers and 562 events by eight species to fruits); these visitors included potential pollinators and seed disperses. Frequent visitors to flowers were the African dor-mouse Graphiurus murinus(53.3%), Nectar bat Mega loglossus woermanni(43.8%), and sunbirds (family Nectariniidae) (2.4%)while those to fruits were Carruther’s mountain squirrel Funisciurus carruthersi(54.1%), L’hoest’s monkeyAllochrocebus l’hoesti(18.7%), and Forest giant pouched rat Cricetomys emini(18.6%). Flower visitors were mainly nocturnal (with birds favoring dusk), while fruit visitors exhibited both diurnal and nocturnal activity patterns. The data indicate that by producing flowers and fruits continuously,E. ventricosum should support animal populations when other flower and fruit resources are scarce.We speculate that establishing these plants in degraded areas may facilitate forest resilience and recovery while providing fallback resources to many species. Such plant species are prime contenders for protection and restoration.
Field research work
Keywords: African Wild Banana; Ensete ventricosum; fruiting phenology; Bwindi Impenetrable National Park